OBJEK WISATA BONO DI SUNGAI KAMPAR KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN RIAU - SANTRI, SANTRI; Rianto, M.Pd, Slamet; Putri, S.Pd., M.Si, Rozana Eka (Pendidikan Geografi, 2014)
Abstracts  This study aims to obtain data and information on : ( 1 ) Potential owned by Bono attractions in the river Kampar District of Teluk Meranti Pelalawan Riau ( 2 ) Obstacles encountered in the development of attractions in the river Kampar Bono District of Teluk Meranti Pelalawan Riau ( 3 ) the efforts made by the government in the development of attractions in the river Kampar Bono District of Teluk Meranti Pelalawan Riau ( 4 ) the efforts made by the community in the development of attractions in the river Kampar Bono District of Teluk Meranti Pelalawan Riau.               The study was qualitative using interviews , observation and research directly spaciousness. Furthermore, the data collected through interview, observation and documentation studies , after the research data obtained through the analysis of data in imaging techniques with words.               The results of the research in the field as follows : a) The potential attraction Bono is Bono has become a national icon in the Province and . b ) Constraints faced in the development of Bono among other attractions : The road that is not on asphalt , Villa or lodgings are still inadequate, eating stalls where tourists are still lacking , there is no public transportation to transport the tourists . c ) The efforts made by the government in the development of attraction Bono is preparing the public to prepare to prepare themselves in order to promote the tourism activities by not lose their identity .